Neural activation differences in amputees during imitation of intact versus amputee movements - Cusack, William F.; Cope, Michael; Nathanson, Sheryl; Pirouz, Nikta; Kistenberg, Robert; Wheaton, Lewis (Frontiers in Human Neuroscience, 2012)
The mirror neuron system has been attributed with increased activation in motor-related cortical areas upon viewing of another’s actions. Recent work suggests that limb movements that are similar and dissimilar in appearance to that of the viewer equivalently activate the mirror neuron system. It is unclear if this result can be observed in the action encoding areas in amputees who use prosthetic devices. Intact subjects and upper extremity amputee prosthesis users were recruited to view video demonstrations of tools being used by an intact actor and a prosthetic device user. All subjects were asked to pantomime the movements seen in the video while recording electroencephalography. Intact subjects showed equivalent left parietofrontal activity during imitation after watching the intact or prosthetic arm. Likewise, when prosthesis users imitated prosthesis demonstrations, typical left parietofrontal activation was observed during planning. When prosthesis users imitated intact actors, a new pattern was revealed which showed greater bilateral parietal and occipital activity during movement planning (p<0.001). This change may be required for prosthesis users to imitate movements in which the limb states between the observed and the observer do not match. The finding that prosthesis users imitating other prosthesis users showed typical left parietofrontal activation suggests that these subjects engage normal planning related activity when they are able to imitate a limb matching their own. This result has significant implications on rehabilitation, as standard therapy involves training with an intact occupational therapist, which could necessitate atypical planning mechanisms in amputees when learning to use their prosthesis.